Analisis Pendapatan dan Kelayakan Usahatani Padi Sawah (Desa Bara Batu Kecamatan Labakkang Kabupaten Pangkep) - Hilda Safitri; Mohammad Anwar Sadat; Azisah Azisah (Universitas Muslim Maros, 2022)
This study aims to determine the income of farmers in lowland rice farming in Bara Batu Village, Labakkang District, Pangkep Regency. This research was carried out for two months, from March to May 2021, which was located in the village of coal stone. The population collection in this study was carried out by simple random sampling or random sampling, namely rice farmers. As for the determination of the sample, namely by taking 20 people who are involved in lowland rice farming. Data collection techniques with questionnaires, interviews, observation and documentation. Data analysis used quantitative and qualitative data analysis. The results showed that the average production amount was 1,897.65 kg with a selling price of Rp. 4.700/Kg. so the average revenue is Rp. 8,918,955.00. Lowland rice farming in Bara Batu Village, Labakkang District, Pangkep Regency, earned an average income of Rp. 5,808,870.00, lowland rice farming in Bara Batu Village, Labakkang District, Pangkep Regency is feasible